Initiation of breastfeeding within one hour of birth among mothers with infants younger than or equal to 6 months of age attending public health institutions in Addis Ababa, Ethiopia - Meseret Ekubay; Aster Berhe; Engida Yisma (BMC, 2018)
Abstract Background Breast milk is comprised of the essential nutrients that an infant needs in the first six months of life. Timely initiation of breastfeeding guarantees that infants receive the colostrum, 'the first breastmilk', which contains antibodies that protect the newborn against diseases. Breastfeeding within the first hour of life prevents newborn death due to sepsis, pneumonia, diarrhea and hypothermia. Although breastfeeding is a common practice in sub-Saharan Africa, evidence show that early initiation of breastfeeding is low. Methods We conducted a cross-sectional study of 583 mothers with infants younger than or equal to 6 months of age attending Maternal and Child Health (MCH) clinics of public health institutions in Addis Ababa, Ethiopia from April to May 2012. A simple random sampling design was used to select the institutions included in this study. Data from mothers of infants were collected using interviewer-administered questionnaire. We analyzed the data to examine factors associated with initiation of breastfeeding within one hour of birth using logistic regression models. Results Of 564 (96.7%, 564/583) mothers who breastfed their infants, 58.3% (329/564) initiated breastfeeding within one hour of birth. In the adjusted analysis, mothers who had three or more infants had about twice higher odds of timely initiation of breastfeeding within one hour of birth (Adjusted Odds Ratio [aOR] 2.10; 95% Confidence Interval [CI]1.04, 4.30) compared with mothers who had one infant. Furthermore, women who started antenatal care at their fourth month of pregnancy or later had a 49.0% higher odds of initiation of breastfeeding within one hour of birth (aOR 1.49; 95% CI 1.01, 2.19) compared to mothers who started antenatal care before their fourth month of pregnancy. Conclusions Initiation of breastfeeding within one hour of birth was low. Initiation of breastfeeding within one hour of birth was highest among multiparous women, mothers aged 30-34 years, and women who began antenatal care at their fourth month of pregnancy or later. Public health officials and health care providers should consider interventions to promote and support early initiation of breastfeeding.